(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Internet of Things (IoT) is considered as one of the greatest significant fields of future technology. It is aimed to join anyone with anything at anywhere. IoT will play a critical role and will change our ways of life, aspirations, and business models. It is vulnerable to numerous security threats. IoT security should move towards in perceiving threats and reacting to attacks. In this research we intent to surveys recent research in the field of IoT security. Another goal of this work is to promote IoT security solutions to reduce security risks that affect IoT users.